ChemInform Abstract: Carbon—Carbon Coupling Reactions Catalyzed by Supported Pd Porphyrins. Issue 42 (14th October 2014) - Bagheri, Omid; Sadegh, Faranak; Moghadam, Majid; Tangestaninejad, Shahram; Mirkhani, Valiollah; Mohammadpoor‐Baltork, Iraj; Safiri, Mahsa
Abstract The shown Pd‐complex (PPC) is supported on Dowex and Amberlite ion‐exchange resins and is used in Heck and Suzuki cross coupling reactions.